Chimeric antigen receptor (CAR)-modified natural killer cell-based immunotherapy and immunological synapse formation in cancer and HIV - Dongfang Liu; Shuo Tian; Kai Zhang; Wei Xiong; Ndongala Michel Lubaki; Zhiying Chen; Weidong Han (Protein & Cell, 2017)
ABSTRACT Cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells contribute to the body’s immune defenses. Current chimeric antigen receptor (CAR)-modified T cell immunotherapy shows strong promise for treating various cancers and infectious diseases. Although CAR-modified NK cell immunotherapy is rapidly gaining attention, its clinical applications are mainly focused on preclinical investigations using the NK92 cell line. Despite recent advances in CAR-modified T cell immunotherapy, cost and severe toxicity have hindered its widespread use. To alleviate these disadvantages of CAR-modified T cell immunotherapy, additional cytotoxic cell-mediated immunotherapies are urgently needed. The unique biology of NK cells allows them to serve as a safe, effective, alternative immunotherapeutic strategy to CAR-modified T cells in the clinic. While the fundamental mechanisms underlying the cytotoxicity and side effects of CAR-modified T and NK cell immunotherapies remain poorly understood, the formation of the immunological synapse (IS) between CAR-modified T or NK cells and their susceptible target cells is known to be essential. The role of the IS in CAR T and NK cell immunotherapies will allow scientists to harness the power of CAR-modified T and NK cells to treat cancer and infectious diseases. In this review, we highlight the potential applications of CAR-modified NK cells to treat cancer and human immunodeficiency virus (HIV), and discuss the challenges and possible future directions of CAR-modified NK cell immunotherapy, as well as the importance of understanding the molecular mechanisms of CAR-modified T cell- or NK cell-mediated cytotoxicity and side effects, with a focus on the CAR-modified NK cell IS.